2020
DOI: 10.1016/j.chest.2020.03.015
|View full text |Cite
|
Sign up to set email alerts
|

A Practical Overview and Reporting Strategies for Statistical Analysis of Survival Studies

Abstract: Survival (time-to-event) analysis is commonly used in clinical research. Key features of performing a survival analysis include checking proportional hazards assumptions, reporting CIs for hazards ratios and relative risks, graphically displaying the findings, and analyzing with consideration of competing risks. This article provides a brief overview of important statistical considerations for survival analysis. Censoring schemes, different methods of survival function estimation, and ways to compare survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 32 publications
0
39
0
Order By: Relevance
“…When the time-toevent of interest is treatment success, it is plausible to assume other treatment outcomes such as 'death',`lostto-follow-up' and`transfer out' were informative censored and thus considered as competing events. Fine and Gray non-parametric test comparing the cumulative incidence functions without requirement of noninformative censoring could be used in such settings [10,[78][79][80][81]. However, application of this method was rare in this review and one of the studies using the method, incorrectly reported hazard ratios rather than subdistribution hazard ratios [52].…”
Section: Discussionmentioning
confidence: 97%
“…When the time-toevent of interest is treatment success, it is plausible to assume other treatment outcomes such as 'death',`lostto-follow-up' and`transfer out' were informative censored and thus considered as competing events. Fine and Gray non-parametric test comparing the cumulative incidence functions without requirement of noninformative censoring could be used in such settings [10,[78][79][80][81]. However, application of this method was rare in this review and one of the studies using the method, incorrectly reported hazard ratios rather than subdistribution hazard ratios [52].…”
Section: Discussionmentioning
confidence: 97%
“…Using Cox proportional hazards modelling, we estimated multivariate-adjusted hazard ratios (HRs) of multiple risk factors on the survival function (short survival used to indicate rapid deterioration), censored when cases were still in care or discharged. Here the censoring was noninformative, where censoring times of the patients are not influenced by their times of their death 31 . We tested whether the proportional hazard assumption stands with inspection of Kaplan-Meier survival curves.…”
Section: Discussionmentioning
confidence: 99%
“…25 Therefore, we selected an accelerated failure time (AFT) model, which does not require an assumption of proportional hazards. 26,27 We tested 3 distributions of the AFT model (Weibull, log-normal, and loglogistic) for goodness of fit using Akaike's information criterion (AIC). We selected the log-logistic model because it produced the best fit model in every country but 2, wherein the AIC did not vary substantially between log-normal and log-logistic distributions.…”
Section: Methodsmentioning
confidence: 99%